2015
DOI: 10.7763/ijssh.2015.v5.550
|View full text |Cite
|
Sign up to set email alerts
|

Public and Private Investment and Economic Development in Iraq (1970-2010)

Abstract: Abstract-Based on the neoclassical growth model of Solow (1956), this study analyses the macroeconomic determinants of economic growth, examining the effect of public and private investment on economic growth in Iraq from 1970 to 2010.Cointegration and error correction models were applied to the time series data, followed by a Johansen cointegration test of trace and maximum eigenvalue statistics to establish long run equilibrium relationships among the variables in the model. This study also estimated an err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…However, it does not have the opposite direction, meaning that in the short run, the increase in investment expenditures has no contribution to local economic growth. Third, Private investment has a positive impact on economic growth (consistent with the research results of Nguyen, Dang and Bui, Hussein & Benin, Phetsavong & Ichihashi, Su 6,18,[26][27][28] ). In terms of enhancing the province's investment environment, Dong Thap is one of the shining examples of the Mekong Delta and the entire nation.…”
Section: Discussionsupporting
confidence: 78%
“…However, it does not have the opposite direction, meaning that in the short run, the increase in investment expenditures has no contribution to local economic growth. Third, Private investment has a positive impact on economic growth (consistent with the research results of Nguyen, Dang and Bui, Hussein & Benin, Phetsavong & Ichihashi, Su 6,18,[26][27][28] ). In terms of enhancing the province's investment environment, Dong Thap is one of the shining examples of the Mekong Delta and the entire nation.…”
Section: Discussionsupporting
confidence: 78%
“…Their empirical findings revealed that, while both public and private investment boost production in the nations studied, the complementary impact of public investment on private investment differed by country. Hussein and Benhin (2015) looked at the impact of public and private investment on Iraqi economic growth from 1970 to 2010. The time series data was applied to cointegration and error correction methods.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The impact of public investment and private investment on economic growth is long been a topic of debate in macroeconomics and development economics, and it has resurfaced in recent years. The influence among these two types of investment on economic growth and social environments is widely recognized (Hussein and Benhin, 2015). Since the dichotomy between public and private investment has an impact on economic growth, it is critical to comprehend the connections between the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the interest rate and inflation, the lower private investment. While, Hussein and Benhin (2015) used Co-integration and error correction models to identify public and private investment and Economic Development in Iraq based on a neoclassical growth framework covered the period from 1970 to 2010. They found that in the long run, private investment, public investment, growth in the labour force and growth in oil revenues affect real gross domestic product (GDP) positively and statistically significant.…”
Section: Literature Reviewmentioning
confidence: 99%